Reverse microemulsion mediated sol-gel synthesis of lithium silicate nanoparticles under ambient conditions: Scope for CO2 sequestration - Khomane, Ramdas B.; Sharma, B. K.; Saha, S.; Kulkarni, B. D. (Chemical Engineering Science, 2006)
We report on the synthesis of nanocrystalline lithium silicate by coupling of sol-gel method in reverse microemulsion. The sample calcined at 800 degrees C gives pure phase lithium metasilicate nanocrystallites. X-ray diffraction and transmission electron microscopy confirmed the formation of nanocrystalline lithium silicate particles with a narrow size distribution. The nanoparticle prepared in the microemulsion shows enhanced CO2 sorption capacity and shorter retention times at higher temperature (similar to 131 ml/g at STP at 610 degrees C which are better than the best known results. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: Adsorption; Carbon dioxide; Microemulsion; particle; separations; sol-gel; surfactant

Nanoreactors for nanostructured materials - Khomane, Ramdas B.; Kulkarni, Bhaskar D. (International Journal of Chemical Reactor Engineering, 2008)
Organized systems such as micelles, reverse micelles, vesicles, polyelectrolyte capsules, liquid crystals, etc., formed through a self-assembling process represent nanoreactors that can be used for preparing nanostructured materials. Besides a fascinating academic subject, these nanoreactors provide a unique way to develop a special type of advanced material for a wide variety of applications in electronics, photonics, biomedical and other areas. The article examines the formation, functioning, properties and special attributes of these nanoreactors with a view towards their engineering analysis, design and possible integration in manufacturing technology.
Keywords: nanoreactors; Nanostructured materials; organized self-assemblies

Preparation and electrochemical characterization of lithium cobalt oxide nanoparticles by modified sol-gel method - Khomane, Ramdas B.; Agrawal, Amit C.; Kulkarni, B. D.; Gopukumar, S.; Sivashanmugam, A. (Materials Research Bulletin, 2008)
Uniformly distributed nanoparticles of LiCoO2 have been synthesized through the simple sol-gel method in presence of neutral surfactant (Tween-80). The powders were characterized by X-ray diffractometry, transmission electron microscopy and electrochemical method including charge-discharge cycling performance. The powder calcined at a temperature of 900 degrees C for 5 h shows pure phase layered LiCoO2. The results show that the particle size is reduced in presence of surfactant as compared to normal sol-gel method. Also, the sample prepared in presence of surfactant and calcined at 900 degrees C for 5 h shows the highest initial discharge capacity (106 mAh g(-1)) with good cycling stability as compared to the sample prepared without surfactant which shows the specific discharge capacity of 50 mAh g(-1). (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: Electrochemical properties; intercalation reactions; Layered compounds; Sol-gel chemistry; X-ray diffraction

Sulfur nanoparticles synthesis and characterization from H2S gas, using novel biodegradable iron chelates in w/o microemulsion - Deshpande, Aniruddha S.; Khomane, Ramdas B.; Vaidya, Bhalchandra K.; Joshi, Renuka M.; Harle, Arti S.; Kulkarni, Bhaskar D. (Nanoscale Research Letters, 2008)
Sulfur nanoparticles were synthesized from hazardous H2S gas using novel biodegradable iron chelates in w/o microemulsion system. Fe3+-malic acid chelate (0.05 M aqueous solution) was studied in w/o microemulsion containing cyclohexane, Triton X-100 and n-hexanol as oil phase, surfactant, co-surfactant, respectively, for catalytic oxidation of H2S gas at ambient conditions of temperature, pressure, and neutral pH. The structural features of sulfur nanoparticles have been characterized by X-ray diffraction (XRD), transmission electron microscope (TEM), energy dispersive spectroscopy (EDS), diffused reflectance infra-red Fourier transform technique, and BET surface area measurements. XRD analysis indicates the presence of alpha-sulfur. TEM analysis shows that the morphology of sulfur nanoparticles synthesized in w/o microemulsion system is nearly uniform in size (average particle size 10 nm) and narrow particle size distribution (in range of 5-15 nm) as compared to that in aqueous surfactant systems. The EDS analysis indicated high purity of sulfur (> 99%). Moreover, sulfur nanoparticles synthesized in w/o microemulsion system exhibit higher antimicrobial activity (against bacteria, yeast, and fungi) than that of colloidal sulfur.
Keywords: Antimicrobial activity; H2S gas; iron chelates; sulfur nanoparticles; w/o microemulsion

Synthesis and magnetic properties of barium-calcium hexaferrite particles prepared by sol-gel and microemulsion techniques - Jotania, R. B.; Khomane, Ramdas B.; Chauhan, C. C.; Menon, Shamal K.; Kulkarni, B. D. (Journal of Magnetism and Magnetic Materials, 2008)
The preparation of W-type hexaferrite particles with the composition BaCa2Fe16O27 by microemulsion and a stearic acid sol - gel method with and without surfactant has been investigated at various sintering temperatures. The structural and magnetic characteristics have been studied by X-ray diffraction ( XRD), a vibrating sample magnetometer ( VSM), scanning electron microscopy ( SEM), thermogravimetric analysis ( TGA), differential scanning calorimetric ( DSC) and Fourier transform infrared ( FTIR) techniques. The effect of sintering temperature on the properties of BaCa2Fe16O27 hexaferrites has been studied. The value of saturation magnetization ( M-s) depends on types of surfactant used. The sample prepared in the presence of polyoxyethylene ( 20) sorbitan monooleat ( Tween 80) shows low saturation magnetization ( M-s 15.10 emu/g), whereas the other sample prepared in the presence of a surfactant cetyltrimethylammonium bromide (CTAB) exhibits high saturation magnetization (M-s = 24.60 emu/g) compared to the normal sample. (C) 2007 Elsevier B. V. All rights reserved.
Keywords: BaCa2Fe16O27; hexaferrite; magnetic property; Microemulsion; Sol-gel method; surfactant

Temperature dependent structural studies and magnetic properties of BaCa2Fe16O27 hexaferrites prepared by stearic acid gel route in presence of SDS surfactant - Joyania, R. B.; Khomane, Ramdas B.; Chauhan, C. C.; Kulkarni, B. D. (Synthesis and Reactivity in Inorganic Metal-Organic and Nano-Metal Chemistry, 2008)
The preparation of BaCa2Fe16O27 hexaferrite powders by a stearic acid gel method with SDS surfactant has been investigated at various sintering temperatures. The samples were characterized by X-ray diffraction, scanning electron microscopy (SEM), TGA, FTIR and vibrating sample magnetometer (VSM). The effect of sintering temperature on properties of BaCa2Fe16O27 hexaferrites was studied. In presence of sodium dodecyl sulfate (SDS) surfactant, the magnetic parameters, like saturation magnetization, coercivity and remanent magnetization, have been calculated from hysteresis loop.
Symposium on New Routes to Inorganic Materials, Films and Nanocrystals held at ICMAT 2007, Singapore, SINGAPORE, JUL 01-06, 2007
Keywords: BaCa2Fe16O27; magnetic properties; stearic acid gel method

Preparation of spherical particles of 1,1-diamino-2,2-dinitroethene (FOX-7) using a micellar nanoreactor - Mandal, Alok Kumar; Thanigaivelan, U.; Pandey, Raj Kishore; Asthana, Srinandan; Khomane, Ramdas B.; Kulkarni, Bhaskar Dattatraya (Organic Process Research & Development, 2012)
The need and preparation of spherical 1,1-diamino-2,2-dinitroethene (FOX-7) particles to meet certain special applications in high explosives and propellant formulation have been illustrated. Preparation of spherical FOX-7 particles by using a microemulsion technique has not been reported in the literature. In the present study, the preparation of spherical FOX-7 particles has been described using the novel concept of a micelle-based nanoreactor. Micelle-based nanoreactors have been prepared using a microemulsion of Triton X-100, cyclohexane, and water. Formation of spherical FOX-7 particles in the reverse micelle reactors have been described in the subsequent sections of this article. It is observed that spherical particles of FOX-7 are formed within 2 h in the microemulsion media. Analysis of the experimental results revealed that the particle size and shape of FOX-7 can be varied by changing the water/surfactant molar ratio in the microemulsion. Spherical particles synthesized by this method have diameters that are generally in the submicrometer to nanometer range. Impact sensitivity (h(50)) of the spherical particles obtained by the fall-hammer method is around 45 cm compared to regular synthesized FOX-7 (i.e., 50 +/- 5 cm) without any change in friction sensitivity, i.e. 36 kg. Loadability of the explosive charges can be enhanced by using these spherical particles of FOX-7.

Sodium-doped lithium zirconate nano squares: synthesis, characterization and applications for CO2 sequestration - Khokhani, Mrinal; Khomane, Ramdas B.; Kulkarni, Bhaskar D. (Journal of Sol-Gel Science and Technology, 2012)
Nano squares of sodium-doped lithium zirconate have been synthesized by a simple citrate based sol-gel method at room temperature in the presence of cetyl trimethylammonium bromide (CTAB) as a surfactant. The structural and morphological properties were investigated by X-ray diffraction (XRD) and Transmission Electron Microscopy (TEM) respectively. XRD analysis of sample calcined at 900 A degrees C for 4 h shows the formation of monoclinic lithium zirconate phase. The TEM shows the interesting morphology of formation of nano squares of sodium doped lithium zirconate sample. The carbon dioxide sorption capacity was carried out by TGA analysis at different high temperatures. It is observed that the sample shows similar to 20 wt% carbon dioxide sorption at higher temperature (650 A degrees C) within 20 min which are better than the known reports.
Keywords: Carbon dioxide; CTAB; Lithium zirconate; Sodium doped lithium zirconate; sol-gel; TEM; XRD

Green synthesis of silver nanoparticles using sunlight - Bhaduri, Gaurav A.; Little, Ross; Khomane, Ramdas B.; Lokhande, Suhas U.; Kulkarni, Bhaskar D.; Mendis, Budhika G.; Siller, Lidija (Journal of Photochemistry and Photobiology A-Chemistry, 2013)
Silver nanoparticles (AgNPs) are currently among the most widely used man-made nanomaterials, present in a huge range of consumer products. Here we report a simple `green' method of AgNP synthesis of using an anionic surfactant without use of any additional reducing agents. It was observed that synthesis of AgNPs at room temperature (25-35 degrees C) using sodium dodecyl sulphate (SDS) and sunlight. The nanoparticles have been characterised using high-resolution transmission electron spectroscopy (HRTEM), UV-vis spectrophotometry, X-ray photoelectron spectroscopy (XPS) and Fourier Transform Infrared Spectroscopy (FTIR) and are found to have an average diameter of 30 nm. The nanoparticles are water soluble and the nature of the process is amenable to scaling up. (c) 2013 Elsevier B.V. All rights reserved.
Keywords: photochemistry; silver nanoparticles; Sodium dodecyl sulphate; XPS

Effect of different temperature on structural, magnetic and dielectric properties of strontium hexaferrite powder synthesised using aloe vera plant extracts - Solanki, Neha; Jotania, R. B.; Khomane, Ramdas B.; Kulkarni, B. D. (Advanced Science Letters, 2016)
M-type SrFe12O19 hexaferrite particles synthesized using the aloe vera plant extract. Biological materials of microorganisms, plants, enzymes have been suggested as an ecological alternative for conventional reagents in physical and chemical methods. In present paper we report effect of temperature on structural, morphology, magnetic and dielectric properties of M-type SrFe12O19 particles synthesised by Green synthesis technique using Aloe vera plant extract. The metal nitrates (Sr and Fe) were dissolved in aloe vera extract solution and then mixture was kept in oil bath at 100 degrees C till it become dry. The obtain dried powder calcined in a wide temperature range, from 450 degrees C to 1150 degrees C for 4 hours in a static air atmosphere. The calcined powders were characterised using various instrumental techniques like Fourier transform infrared spectroscopy (FTIR) X-ray diffractometry (XRD), Scanning electron microscopy (SEM), energy dispersive X-ray spectroscopy (EDX), Vibrating Sample Magnetometry (VSM), and dielectric measurements. XRD, FTIR, SEM, Magnetic and dielectric measurements were carried out at room temperature. XRD analysis confirms the formation of mono phase of strontium hexaferrite at 1150 degrees C.
3rd International Conference on Nanotechnology, Pune, INDIA, OCT 14-15, 2014
Keywords: Aloe Vera Extract; green synthesis; M-Type Hexaferrite; Strontium Hexaferrite

Nanostructure oxygen carrier used in chemical looping combustion process-A review - Badadare, Mansing M.; Adbale, Naina M.; Khomane, Ramdas B.; Kale, Ganesh R. (Advanced Science Letters, 2016)
Chemical looping combustion (CLC) is an emerging technology with inherent separation of CO2 from combustion of fuels. In this technique contact of air and fuel for combustion is restricted by providing oxygen through oxygen carrier (DC). The functional efficiency of CLC process mainly depends on the ability of oxygen carrier and it's reactivity, which undergoes repeated oxidation and reduction cycles. Nanostructure metal oxides have shown great potential application in the field of chemical looping combustion due to their high surface to volume ratio and enhanced structural properties. Synthesis technique of nanostructure metal oxides, their role as oxygen carrier, their reactivity with fuels along with their structural stability are reviewed herein. The contribution of various operating conditions on nanostructure oxygen carrier are considered in this review. These operating conditions and synthesis routes are summarized and classified according to metal oxides.
3rd International Conference on Nanotechnology, Pune, INDIA, OCT 14-15, 2014
Keywords: Chemical looping combustion; CO2 Emission; Metal Oxide; Nanostructure; Oxygen Carrier